Effect of Mitochondrial Tu Translation Elongation Factor on Water-holding Capacity of Qinchuan Cattle Meat during Postmortem Aging - SI Jianfang, ZHANG Jing, GAO Shuang, MA Jiarong, CAO Songmin, LI Yalei, LUO Ruiming (Shipin Kexue)
In order to investigate the effect of mitochondrial Tu translation elongation factor (TUFM) expression on the water-holding capacity (WHC) of meat during the postmortem aging of Qinchuan cattle meat, changes in the pH, storage loss, centrifugal loss, cooking loss, and water distribution of the longissimus dorsi of Qinchuan cattle as well as its myofibrillar protein degradation were determined after different aging durations at 4 ℃. Besides, TUFM expression and content as well as beclin 1 expression were examined after 0, 96 and 192 h of aging. The results showed that myofibrillar protein was degraded during the postmortem aging process, and there was a close relationship between the expression of TUFM and beclin1 protein and the WHC of beef. Proteomics revealed consistent changing trends between the expression of TUFM and its content. In general, beclin1 protein expression, storage loss, centrifugal loss, and cooking loss initially increased and subsequently decreased, whereas the opposite was true for pH. Pearson’s correlation analysis showed that the expression of TUFM was highly significantly positively correlated with low-field nuclear magnetic resonance peak area ratio P2b and beclin 1 protein expression (P 0.05). Through proteomics, 23 differential proteins related to TUFM were identified, and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that the differential proteins could mediate cellular autophagy by participating in energy metabolism through a variety of pathways. Pearson’s correlation analysis showed that five differential proteins (ATP5F1D, EEF1A2, GSPT1, NDUFB5, and SUCLG1) were significantly correlated with WHC (P < 0.05, P < 0.01). From these analyses, it is clear that there are six proteins including TUFM that affect the WHC of meat by affecting cellular autophagy positively or negatively through various pathways such as energy metabolism and oxygen transport.